Architects' sketchbooks - Jones, Will. (London : Thames & Hudson, 2011)
This survey presents the private sketchbooks of a wide international spectrum of architects, who use the medium to express their spatial ideas while revealing their unique thought processes.
Keywords: Architectural drawing; Architectural rendering